La sentencia del certamen poético de Sant Just (1438): edición y estudio preliminar. - MARTÍ, SADURNÍ (Scripta, 2017)
This paper edits for the first time the sentence of a medieval poetical contest celebrated at the Sant Just church of Barcelona, in June 1438. The chosen thema was the lament against Love and the jewel to be awarded was offered by Bartomeu Castelló. We know the poets Guillem and Joan Berenguer de Masdovelles participated. The most remarkable aspect of this verdict, written in Catalan and Latin, and copied in the songbook of the Marquis of Barberà, is that not only presents the starting speech-preaching (which includes a para-theatrical dialogue), but also a commentary of the pieces that competed.